Variance in the radial distribution of nuclear matter between 56Ni and 58Ni inferred from a model-independent Sum-of-Gaussian analysis of elastic proton scattering data - X. Liu; P. Egelhof; O. Kiselev; M. Mutterer (Physics Letters B, 2020)
Differential cross sections for p-Ni56 and p-Ni58 elastic scattering, measured at low momentum transfer and at projectile energies of about 400 MeV/u with beams stored in the Experimental Storage Ring (ESR) at GSI, Darmstadt, have been analyzed up to |t|=0.06 (GeV/c)2 applying the model-independent Sum-of-Gaussians (SOG) method based on the Glauber multiple-scattering theory. The rms point matter radius of the self-conjugate doubly magic radioactive Ni56 nucleus was deduced to be 3.62(6) fm, to be compared to the known radius of the stable Ni58 nucleus, 3.67(7) fm. Although the radii of both nuclei differ only slightly, and there is close agreement of the matter radii of Ni58 from former analyses using phenomenological parametrizations of the matter distribution, the SOG method was capable of elucidating pronounced differences in the shapes of the radial matter distributions between both nuclei. Consequences for the understanding of nuclear structure in the vicinity of the N=Z=28 magic shell are briefly discussed.